Multiple ligand simultaneous docking (MLSD): A novel approach to study the effect of inhibitors on substrate binding to PPO. (December 2015) - Raghavendra, S.; Aditya Rao, S.J.; Kumar, Vadlapudi; Ramesh, C.K.
Graphical abstract: Highlights: Concurrent interactions between the substrate and inhibitors with the enzyme polyphenol oxidase were studied. Variation in binding dynamics of the substrate with polyphenoloxidase was compared in the presence and absence of an inhibitor. The present work is an extension of our previous work entitled Characterization of poly phenol oxidase in two in vitro regenerated cultivars of Mucuna: Mucuna pruriens L. and Mucuna prurita H. The results of in-silico studies are in support with the results of in-vitro studies. Abstract: Multiple ligand simultaneous docking, a computational approach is used to study the concurrent interactions between substrate and the macromolecule binding together in the presence of an inhibitor. The present investigation deals with the study of the effect of different inhibitors on binding of substrate to the protein Polyphenoloxidase (PPO). The protein was isolated from Mucuna pruriens and confirmed as tyrosinases involved inl -DOPA production. The activity was measured using different inhibitors at different concentrations taking catechol as substrate. A high-throughput binding study was conducted to compare the binding orientations of individual ligands and multiple ligands employing Autodock 4.2. The results of single substrate docking showed a better binding of urea with the binding energy of −3.48 kJ mol −1 and inter molecular energy of −3.48 kJ mol −1 while the results of MLSD revealed that ascorbic acid combined with the substrate showed better inhibition with a decreased binding energy of −2.37 kJ mol −1 .